Optimalisasi Peran Kader Posyantek dalam Pemanfaatan Sumber Daya Alam Lokal Di Desa Teluk Bakau Kecamatan Gunung Kijang Kabupaten Bintan Kepri - Suswaini, Eka; Uperiati, Alena; Purnamasari, Dwi Amalia; Chahyadi, Ferdi; Nurfalinda, Nurfalinda; Hekso, Anton (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
The Bintan Regency Government through the Village Community Empowerment Service (PMD) established Posyantek (Pos Technology Services) in 2018. Posyantek is a Technology Service that is spread out from the smallest villages, sub-districts and districts. Based on the Minister of Home Affairs regulation No. 20 of 2010 concerning Community Empowerment through Appropriate Technology Management and also Minister of Home Affairs Instruction No. 24 of 1998 concerning Posyantekdes operations. The purpose of establishing a posyantek is how to improve the welfare of the community. Posyantek has various main types which include providing technical services, information, and promotion of various types of TTG to the community, increasing the quality and quantity of various types of products produced by the community, both small and medium enterprises (SMEs), posyantek is also expected to be a bridge for the community to use TTG in the context of utilizing TTG (Appropriate Technology). The purpose of community service is carried out as an effort to support the important role of the presence of technology in community life as one of the factors driving change and also accelerating development both in the economic, and social and cultural fields. In the process of implementing Posyantek Posyantek operations in the Regency of Bintan is developing a process of designing activities programs, in line with this the need for synergy of interference and support from related parties including educational institutions in the Maritime University of Raja Ali Haji. Assistance and training are given to posyantek cadres in carrying out work programs in accordance with the output expected by the government and the community.